Case Report: Management of Chronic Supurative Otitis Media Cholesteatoma Type with Recurrent Brain Abscess Complication - Khairani Ayunanda Ikhlas; Yan Edward (Faculty of Medicine, University of Jember, 2022)
Introduction: Chronic suppurative otitis media is broadly defined as chronic inflammation that involved mucose of middle ear and mastoid air cells. The most commonly encountered intracranial complication from chronic suppurative otitis media is meningitis followed by brain abscess. Antibiotics are quite effective in early and late cerebritis stage. Surgical intervention is essential once the abscess’s capsule is formed. Case Report: Reported a case of a 22-year-old male diagnosed with chronic suppurative otitis media auris dextra suspected cholesteatoma type with cerebral abscess complications. The managements are cerebral abscess drainage followed by canal wall down mastoidectomy. In patient, Recurrent cerebral abscess formed. Conclusion: Chronic suppurative otitis media with complications of cerebral abscess is treated with abscess drainage if the abscess size is >2cm and followed by canal wall down mastoidectomy. Otogenic brain abscess due to chronic suppurative otitis media can occur repeatedly if abscess antibiotic therapy was/were inadequate Keywords: otogenic brain abscess, mastoidectomy, chronic suppurative otitis media, abscess drainage